2018
DOI: 10.1002/ijch.201700045
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloid Synthesis via Gold‐Catalyzed Carbon‐Carbon Bond Formation Using Enamine‐type Nucleophile

Abstract: In this account, various types of cyclizations/cycloisomerizations of alkyne substrates with internal enamine‐type nucleophiles including enamide, enaminone, enaminoester and in situ generated enamine in the presence of electrophilc transition metal catalysts (Pt, Rh, Cu, Au) are firstly introduced. Then, the applications of the gold‐catalyzed reactions in the synthesis of an array of alkaloids are discussed. These natural products feature heterocyclic structural motifs such as pyridine, azaanthraquinone, pyri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…In 1987, the first homogeneous gold-catalyzed addition of nucleophiles to alkynes was realized by the group of Utimoto using sodium tetrachloroaurate dihydrate. , One decade later, Teles et al and Tanaka et al demonstrated the possibility of activating alkynes using gold­(I) complexes. From that point, the field of gold­(I) catalysis started to gain momentum year after year and still today remains one of the most active areas of research in organometallic chemistry. , This comes as a consequence of the ability of gold­(I) complexes to activate π bonds in a very selective manner. Its potential, attributed partially to relativistic effects, is illustrated by the wide molecular complexity that can be built through the gold­(I)-catalyzed cycloisomerization of enynes (Scheme ). …”
Section: Introductionmentioning
confidence: 99%
“…In 1987, the first homogeneous gold-catalyzed addition of nucleophiles to alkynes was realized by the group of Utimoto using sodium tetrachloroaurate dihydrate. , One decade later, Teles et al and Tanaka et al demonstrated the possibility of activating alkynes using gold­(I) complexes. From that point, the field of gold­(I) catalysis started to gain momentum year after year and still today remains one of the most active areas of research in organometallic chemistry. , This comes as a consequence of the ability of gold­(I) complexes to activate π bonds in a very selective manner. Its potential, attributed partially to relativistic effects, is illustrated by the wide molecular complexity that can be built through the gold­(I)-catalyzed cycloisomerization of enynes (Scheme ). …”
Section: Introductionmentioning
confidence: 99%